Ефективність гербіцидів при вирощуванні сої в Степу України - Васільєв, Богдан Віталійович; Vasiliev, Bohdan (ЦНТУ, 2025)
Сільськогосподарським підприємствам при вирощуванні сої рекомендуємо вносити гербіцид Прімекстра TZ Голд у нормі 4,5 л/га під передпосівну культивацію + Міура у нормі 0,6 л/га у фазу 3 – 5 листків + Хармоні 8 г/га. Це забезпечує отримання умовно чистого прибутку на рівні 23888 грн./га, а рівень рентабельності становить 142,4%. The main goal of the work is to study the effectiveness of herbicides in soybean crops. When growing soybeans, we recommend that agricultural enterprises apply the herbicide Primextra TZ Gold at a rate of 4.5 l/ha for pre-sowing cultivation + Miura at a rate of 0.6 l/ha in the 3-5 leaf phase + Harmony 8 g/ha. This ensures a conditional net profit of 23,888 UAH/ha, and the profitability level is 142.4%.
The effectiveness of herbicides in growing soybeans in the Steppe of Ukraine
Keywords: соя; гербіциди; врожайність; soybean; herbicides; yield